Factors Associated With Major Complications and Mortality During Hospitalization in Patients With Ankylosing Spondylitis Undergoing Surgical Management for a Spine Fracture. Issue 7 (September 2022) - Ull, Christopher; Yilmaz, Emre; Hoffmann, Martin F.; Reinke, Charlotte; Aach, Mirko; Schildhauer, Thomas Armin; Kruppa, Christiane
Study design: Retrospective study. Objectives: To analyze factors associated with major complications (MC) in patients with ankylosing spondylitis (AS) undergoing surgical management for a spine fracture. Methods: Included were all persons with spine fractures and AS in a teriary health care center between 2003 and 2019. Clinical data and MC were characterized with descriptive characteristics. Multivariable analyses were used to find factors associated with MC. Results: In total, 174 traumatic fracture incidents in 166 patients with AS were included, with a mean patient age of 70.7 ± 13.1 years. The main reason for spine fracture was minor trauma (79.9%). Spinal cord injuries (SCI) were described in 36.7% of cases. The majority of patients (54.6%) showed more than one fracture of the spine, with cervical fractures being the most common (50.5%). Overall, the incidences of surgical site infection, implant failure, nosocomial pneumonia (NP), and mortality were 17.2%, 9.2%, 31%, and 14.9%, respectively. ICU stay > 48 hours was associated with MC (including death). Posterior approach for spondylodesis, ICU stay > 48 hours and cervical SCI were related to MC (excluding death). Age > 70 years, NP and Charlson comorbidity index > 5 points were associated with in-hospital mortality. Conclusions: Patients with AS and surgical treatment of spine fractures are at high risk for MC. Therefore, our results might give physicians better insight into the incidence and sequelae of major complications and therefore might improve patient and family expectations.